Exergaming iImproves self-efficacy in sustaining physical activity among sedentary university students - Hafzan, Yusoff (Kementerian Pendidikan Tinggi (KPT), Malaysia, 2021)
Link to publisher's homepage at http://www.mohejournal.com/index.php/mohe